Superficial siderosis due to papillary glioneuronal tumor - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
Superficial siderosis of the central nervous system is a rare, progressive, irreversible and debilitating neurological disease characterized by the deposition of haemosiderin in the leptomeninges and the subpial layers of the brain and spinal lord. The main clinical findings are progressive bilateral sensorineural hearing loss, cerebellar ataxia and pyramidal tract signs. The present report describes a 49-year-old woman who presented with intermittent headache of 5 years duration. The pain had become more severe in the previous 6 months. Neurological examination revealed nothing abnormal. Computed tomography showed a cystic mass with apparent internal haemorrhage in the right frontal lobe and T-2-weighted magnetic resonance imaging showed material of low signal intensity coating the entire surface of the brain. The mass was completely excised via craniotomy. A histopathological study identified the mass as a papillary glioneuronal tumour. The patient recovered well and is still neurologically normal 1 year later, This is the first documented case of superficial siderosis caused by this type of tumour. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: ataxia; papillary glioneuronal tumour; siderosis; CENTRAL-NERVOUS-SYSTEM; CNS